Changes in als2 expression leads to different outcomes on the expression of two NF-kB targeted genes in N2a and C2C12 cell lines - Ozansoy, Mehmet; Ozansoy, Muzaffer Beyza (Logos Medical Publishing, 2019)
Objective: Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder affecting spinal and cortical motor neurons. Motor neuron degeneration leads to progressive muscular atrophy. Als2 (alsin) is one of the causative genes of ALS and UXT gene is an interacting partner of Als2. Since UXT is a known cofactor in NF-?B enhancesome, we aimed here to compare the effects of Als2 silencing on NF-?B activity by using N2a and C2C12 cell lines. Methods: Mouse neuroblastoma cells (N2a) and myoblast cell lines (C2C12) were used. Als2 was silenced by RNAi and UXT, A20 and IL8 expressions were measured by qRT-PCR. Data were statistically evaluated by Student t-test. Results: A 73.4% decrease was observed in Als2 expression in N2a cells, whereas 73.7% decrease in the C2C12 cells was found. UXT expression in Als2-silenced N2a cells was found to be decreased by 40%, while a 9-fold increase in C2C12 cells was detected. IL8 expression demonstrated a 84% decrease in N2a cells. On the other hand,IL8 expression increased 50-fold in C2C12 cells. A20 expression increased by 65% in N2a cell line, and increased 10 fold in C2C12 cell line. Conclusion: We have concluded that silencing Als2 gene over UXT on exerts different effects on NF-?B pathway We arrived at this conclusion because changes in the expressions of the IL8 and A20 genes differ in both cell lines. In addition, the link between Als2 and UXT is shown again in both cell lines and it is understood that the silencing Als2 may give rise to different results as for neuronal cells and muscle cells.

Amaç: Amiyotrofik Lateral Skleroz (ALS) spinal ve kortikal motor nöronları etkileyen nörodejeneratif bir hastalıktır. Motor nöron dejenerasyonu ise kaslarda ilerleyici atrofiye neden olur. ALS’ye neden olan genlerden biri Als2 (alsin) genidir ve UXT geni de Als2 ile etkileşimde olan genleden biridir. UXT proteininin NF-?B kompleksinde kofaktör olarak rol aldığı da bilinmektedir. Bu çalışmadaki amacımız, Als2’nin susturulmasının NF-?B aktivitesindeki olası etkilerini N2a ve C2C12 hücre hatlarında karşılaştırmaktır. Yöntem: Bu çalışmada, fare nöroblastoma hücreleri (N2a) ile fare miyoblast hücreleri (C2C12) kullanıldı. Söz konusu hücrelerde Als2 geni RNAi ile susturuldu ve UXT, IL8 ve A20 genlerinin ekspresyonları qRT-PCR ile ölçüldü. Veriler Student t-test kullanılarak istatistiksel olarak değerlendirildi. Bulgular: N2a hücrelerinde Als2 ekspresyonundaki azalış %73,4 olurken C2C12 hücrelerinde %73,7’lik bir düşüş gözlendi. Als2 geni susturulmuş N2a hücrelerinde UXT seviyesi %40 azalırken, C2C12 hücrelerinde 9 katlık bir UXT artışı saptandı. IL8 ekspresyonu N2a hücrelerinde %84’lük bir düşüş gösterdi, ancak C2C12 hücrelerinde IL8 ekspresyonu 50 katlık bir yükseliş kaydetti. Öte yandan A20 ekspresyonu N2a hücre hattında %65 artarken, bu artış C2C12 hücre hattında 10 misli olarak gerçekleşti. Sonuç: Als2 geninin susturulmasının UXT üzerinden NF-?B yolağına olan etkilerinin farklı olduğu sonucuna ulaşılmıştır. Bu sonuca IL8 ve A20 genlerinin ekspresyonlarındaki değişimlerin her iki hücre hattında da farklılık göstermesi üzerinden varılmıştır. Ayrıca Als2 ve UXT arasındaki bağlantı her iki hücre hattında da tekrar gösterilmiş ve Als2’nin susturulmasının nöronal hücreler ile kas hücreleri açısından farklı sonuçlar doğurabileceği de anlaşılmıştır.
Als 2 ekspresyonunun NF-kB hedefli iki gen üzerindeki olası etkisinin n2a ve c2c12 hücre hatlarında araştırılması
Keywords: ALS; Als2; NF-kB; N2a; C2C12